Cutting On Existing Bonded Post-Tensioned Slabs: Safety Precautions, Procedures and Execution - Irwanto, Rachmad; Hanif, Hanif (International Journal of Integrated Engineering, 2023)
Post-formed cut-off or cutting of the post-tensioned slabs is a common practice during post-tensioning work. However, cutting on existing post-tensioned slabs must be done carefully to avoid severe damage to the building. The measurements during the design review are critical in considerations of post-cutting conditions, variations between shop drawings and site, possible grouting failure and excessive deformation. This paper presents a successfully execution of cutting operations on bonded post-tensioned slabs without compromising the structural strength and serviceability. There are procedures and requirements that need to be considered prior to cutting at the design stage, prior to cutting at the site and at slab cutting stage. The safety precautions are necessary for unintentional scenarios that require immediate action. Cutting the slab creates potential hazards. It was found that the grouting material plays an important role not only in solidifying the concrete but also in forming a secondary anchorage mechanism. Therefore, selection of suitable grouting material should be based on the dimension of the locking area. In contrast to unbonded post-tensioned slabs, bonded post-tensioned slabs do not require de-tensioning and re-tensioning.